COMMUNITY SERVICE EDUCATION FOR POSTPARTUM MOTHERS THROUGH THE USE OF TRADITIONAL HERBS AND LOCAL NUTRITION TO ACCELERATE MATERNAL RECOVERY AT THE DELIMA CLINIC - Ruminta Sirait; Aspiati; Analysis Giawa (Cattleya Darmaya Fortuna, 2023)
The postpartum period is a critical phase that requires optimal recovery, where improper maternal care and food restrictions can hinder wound healing. This community service activity aims to improve the knowledge, attitudes, and practical skills of postpartum mothers regarding maternal self-care by utilizing traditional herbal medicine and local nutritional resources. Carried out at the Delima Clinic by an academic team from STIKes Darmo Medan, this intervention involved public health counseling and interactive focus group discussions, and was evaluated through a pre-test and post-test quantitative design. The results showed a significant increase in participants' awareness, effectively eliminating traditional food taboos, and empowering mothers to safely utilize local nutrients to speed up the healing of perineal wounds. In conclusion, structured education on safe local food sources and traditional herbal medicine serves as an effective strategy to optimize the recovery and well-being of postpartum mothers.